Assessment of cytotoxicity of clear aligners coated with zinc oxide nanoparticles - Indu Ravi; Vignesh Kailasam (Journal of Oral Biology and Craniofacial Research)
Background: Coating with nanoparticles can have clinical benefits like anti-bacterial activity and therefore an improvement in oral hygiene. However, the toxicity of these coatings is not known. The aim was to assess and compare the viability of human gingival fibroblasts (HGFs) of clear aligners coated with zinc oxide nanoparticles of different sizes. Methods: Zinc oxide nanoparticles of 30 nm, 60 nm & 90 nm were sputter coated on five aligner samples and were compared with 5 uncoated samples. The thickness of the coating was standardized at 100 nm. The cytotoxicity on HGFs was assessed at day 0, 7 and 14 using assay ([3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide]). Results: The coated aligners exhibited “slight-cytotoxicity” on day 7 and day 14 compared to the uncoated aligners which were categorized as “no cytotoxicity”. Though the cell viability decreased in both the coated and uncoated aligners from day 0 to day 7 to day 14, this decrease was statistically significant for the coated aligners only. (p < 0.05) The greater cytotoxicity observed for the coated aligners was statistically significant only on day 14 (p < 0.001). Within the coated aligners, the 90 nm coating showed the least cytotoxicity, when compared with 60 nm and 30 nm at the time points measured, but this difference was significant only between the 90 nm and 60 nm group on day 14. Conclusion: The mean decrease in cell viability for the uncoated aligner within the “no cytotoxicity range” while it was within the “slight cytotoxicity range” for the coated aligner. An increase in particle size demonstrated lesser cytotoxicity. ,.Zinc oxide coated aligners should be used with caution after day 7 even though there is only slight toxicity.